(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The aim of this study is to determine the burnout levels of female personnel working in the Provincial Directorates of Youth and Sports and to compare them in terms of some variables. In this study, 117 female personnel with a mean age of 39.68 ± 9.37 who were selected by random sampling who were working in the provincial center of Ankara and in some selected districts (Mamak, Çankaya, Sincan, Keçiören, Demetevler) participated in the study. Seven of the research questions developed by the researcher for determining the demographic data personal information form was used. Maslach Burnout Scale was used to determine burnout levels of the participants. In the analysis of data, frequency and percentage calculations were made for the demographic characteristics of the research group. Descriptive statistics of the depleted levels of the female staff working in the Provincial Directorates of Youth and Sports have been demonstrated. Independent single-sample test (t-test) and one-way ANOVA (OneWay ANOVA) were used to examine whether participants' burnout levels differ according to variables. In the analysis of the data, a significance level of 0.05 was adopted. According to the results of the analysis, the t-test for the comparison of the burnout scale sub-dimensions and the ANOVA results showed that the emotional exhaustion, depersonalization, and personal accomplishment sub-dimensions of the female staff working in the Provincial Directorates of Youth and Sports age group, marital status, having a child, education status, occupation It does not differ according to working style and working year. As a result, the female staff working in the Provincial Directorates of Youth and Sports have the highest level of burnout in the middle level of emotional exhaustion and their burnout levels are 22-30, 31-40, 41-50 and 51 years of age and older, married, or single. whether they have children, have lower or lower secondary or higher levels of education, high school or higher or above, occupational status as coach, civil servant, cleaning officer or security officer, work forms shall be permanent, contract, service, or subcontractor -10, 11-15 or 16 years and may be said to be unchanged.